Effect of Fenugreek (Trigonella foenum-graecum L.) Extract on Early Growth Parameters of Phaseolus vulgaris L. - Soliman, Ashraf; Naima Mohamed; Fadwa Almiar; Awatef Shlibak (AlQalam Journal of Medical and Applied Sciences, 2026)
The effect of fenugreek seed extract on early seedling growth of Phaseolus vulgaris L. was studied in the present work. Six concentrations of extract (0% control, 5%, 10%, 20%, 30%, and 40%) were used, and growth parameters were observed daily for 14 days. The results were indicative of a clear concentration-dependent effect. The highest plumule elongation value was observed at 40%, 5.00 cm (a 67% increase compared to the control 2.97cm). Root length was also maximum at 10% concentration (8.00cm), and the maximum number of roots was also observed at 5% concentration (23 roots). Two-way Repeated Measures ANOVA showed significant effects of extract concentration, time, and their interaction (p < 0.05), indicating that seedling responses changed over the duration of the experiment. Tukey’s HSD post-hoc analysis revealed significant differences between treatments and varying maxima across growth parameters. Fenugreek seed extract contains bioactive chemicals that influence shoot and root growth, suggesting its potential as a natural biostimulant for leguminous crops.